The Effect of Work Life Balance, Compensation And Work Environment On Employee Loyalty At Telkom Schools Regional Medan - Yonathan Natanael Waruwu; Tri Bobi Boni Pasius Sianipar; Roy Dedi Ansarika; Tika Arizona Febriani (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2026)
This study aims to examine the effect of work-life balance, compensation, and work environment on employee loyalty at Telkom Schools Regional Medan. Employee loyalty is a crucial factor for organizational sustainability, particularly in the context of modern human resource management. This research employs a quantitative approach with a causal associative design. The population consisted of all 85 employees of Telkom Schools Regional Medan, and a saturated sampling technique was applied so that the entire population served as the research sample. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using multiple linear regression with SPSS. The results show that work-life balance, compensation, and work environment simultaneously have a positive and significant effect on employee loyalty. Partially, each independent variable also demonstrates a positive and significant influence on employee loyalty. The coefficient of determination indicates that 64.2% of employee loyalty is explained by the three independent variables, while the remaining 35.8% is influenced by other factors outside the model. These findings highlight the importance of implementing balanced work-life policies, fair compensation systems, and a supportive work environment to strengthen employee loyalty.